2011
DOI: 10.3851/imp1953
|View full text |Cite
|
Sign up to set email alerts
|

A Case of a Potential Drug Interaction between Clobazam and Etravirine-Based Antiretroviral Therapy

Abstract: The cytochrome P450 isoforms primarily involved in clobazam metabolism are CYP3A4 and 2C19. Drugs that modulate these enzymes would then be expected to alter the exposure of clobazam and its major metabolites. Etravirine, a second-generation non-nucleoside reverse transcriptase inhibitor has been shown to induce CYP3A4, while inhibiting CYP2C9 and CYP2C19. We report a case in which a potential drug interaction between clobazam and etravirine may have led to increased concentrations of clobazam and its pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…CBD inhibits CYP 2C19 and CYP 3A4, which catalyze the metabolism of nCLB . This inhibition likely leads to an accumulation of nCLB, which studies have shown to be about 20–100% as potent as CLB .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CBD inhibits CYP 2C19 and CYP 3A4, which catalyze the metabolism of nCLB . This inhibition likely leads to an accumulation of nCLB, which studies have shown to be about 20–100% as potent as CLB .…”
Section: Discussionmentioning
confidence: 99%
“…CBD inhibits CYP 2C19 and CYP 3A4, which catalyze the metabolism of nCLB. [14][15][16][17] This inhibition likely leads to an accumulation of nCLB, which studies have shown to be about 20-100% as potent as CLB. 12 In addition, genetic polymorphism exists for CYP 2C19 expression, resulting in rare poor CYP 2C19 metabolizers, 24 in which plasma levels of N-desmethylclobazam are fivefold higher in plasma than in CYP 2C19 extensive metabolizers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clobazam is similarly hepatically metabolized and there is a case report of neurotoxicity from increased concentrations of clobazam when co-administered with the NNRTI etravirine. [53] Felbamate and vigabatrin are normally reserved for refractory epilepsy cases and the associated adverse side effects of aplastic anemia and liver failure (felbamate) and vision loss (vigabatrin) could be particularly devastating in the HIV population. Zonisamide is an attractive candidate because its once daily dosing is favorable for compliance, particularly in patients with neurocognitive impairment.…”
Section: Treatmentmentioning
confidence: 99%
“…Four of these cases 41,42,84,85 had N-desmethylclobazam concentrations >3000 ng/mL; 3 cases 41,42,85 had concentrations > 4 times 3000 ng/mL, including 1 case 85 >10 times 3000 ng/mL. N-desmethylclobazam concentrations were not measured in 2 cases, 83,86 but their clobazam concentrations were >3000 ng/mL or 10 times higher than the upper recommended limit of 300 ng/mL.…”
Section: Literature Reviewmentioning
confidence: 87%